2013
DOI: 10.4103/0971-3026.113614
|View full text |Cite
|
Sign up to set email alerts
|

Role of quantitative pharmacokinetic parameter (transfer constant: Ktrans) in the characterization of breast lesions on MRI

Abstract: Background:The semi-quantitative analysis of the time–intensity curves in dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has a limited specificity due to overlapping enhancement patterns after gadolinium administration. With the advances in technology and faster sequences, imaging of the entire breast can be done in a few seconds, which allows measuring the transit of contrast (transfer constant: Ktrans) through the vascular bed at capillary level that reflects quantitative measure of porosity/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…In this study, a statistically significant difference was observed in K trans between the benign and malignant groups (P=0.032, 1.14 min –1 vs . 1.91 min –1 ), which was consistent with previous reports ( 21 , 22 ). However, the sensitivity and specificity were 59.6% and 66.7%, respectively, which were lower than those of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a statistically significant difference was observed in K trans between the benign and malignant groups (P=0.032, 1.14 min –1 vs . 1.91 min –1 ), which was consistent with previous reports ( 21 , 22 ). However, the sensitivity and specificity were 59.6% and 66.7%, respectively, which were lower than those of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…At a lower field strength, one has to compromise on using either a high temporal resolution suitable for PK analysis or a high spatial resolution for detailed morphologic assessment. Our findings are in good agreement with prior studies at 1.5 and 3T, which demonstrated the potential of PK parameters to aid in the differentiation of benign from malignant tumors [ 14 , 18 , 32 , 44 , 45 , 46 , 47 ]. We integrated the information from quantitative PK analysis to established reporting guidelines, i.e., BI-RADS, showing that PK-enhanced BI-RADS improved diagnostic accuracy from 88.4% to 97.7% by reducing false-positive findings.…”
Section: Discussionsupporting
confidence: 91%
“…Quantitative information derived from full-length DCE-MRI acquisitions (approximately 10 min in length) has demonstrated added benefit in distinguishing malignancies [ 5 , 13 , 24 ]. Specifically, the volume transfer constant, K trans , has been shown to statistically distinguish malignant from benign lesions, including in the ultra-fast DCE-MRI setting with superior temporal resolution [ 13 , 24 , 25 , 26 ]. Still, quantitative DCE-MRI can be challenging to incorporate into the clinical workflow as it requires higher temporal resolution data which comes at the expense of missing spatial resolution in the images required by radiologists.…”
Section: Introductionmentioning
confidence: 99%